(untitled) (Research, Society and Development, 2021)
This study aimed to identify nurses’ perception of primary health care about the use of computers and information technology in their daily activities. It is a field research, exploratory, descriptive, with a qualitative approach, through the application of a form via Google Docs, containing guiding questions, made by the researcher, based on the literature. The sample consisted of 19 nurses with ages varying from 22 to 55 years old, mostly female. When asked if they had a specific computer course, most did not have it considering their knowledge as a basic level. However, it was found that the computer and information technology assist in the organization and planning of care, allowing the optimization of work, making not only the assistance more agile but also with greater quality, safety and resolution. However, these tools were limited for technical and operational reasons.